Differential malic acid degradation by indigenous and commercial Saccharomyces cerevisiae wine strains - Pereira, Leonor (2007)
One thousand six hundred and twenty yeast isolates were obtained from spontaneous fermentations performed with grapes collected in three vineyards of the Vinho Verde Wine Region in northwest Portugal during three subsequent harvest seasons. All isolates were analyzed by mitochondrial DNA restriction fragment length polymorphism (mtDNA RFLP) and a pattern profile was verified for each isolate, resulting in a total of 294 different profiles, all revealed to belong to the species Saccharomyces cerevisiae. A remarkable heterogeneity of phenotypical traits was found when this collection of indigenous S. cerevisiae strains was screened regarding ethanol tolerance, H2S production, capacity to utilize acetic and malic acid. Malic acid, together with tartaric acid, are the most abundant organic acids in wine contributing to its acidic taste. Excess malic acid removal is of enological interest in this wine region. From the screening of 294 strains, only 3 (318, 319 and 320) showed enhanced malic acid consumption in combination with other desirable phenotypic traits. Their fermentative profiles in a synthetic must medium containing glucose (20%, w/v) and D,L-malic acid (0.6%, w/v) were very similar to the ones observed for the commercial strains QA23 and 71B, but considerable differences were found regarding the activity of key enzymes involved in the metabolism of malic acid (malic enzyme, malate dehydrogenase, fumarase). The best malic acid degrading strain was 71B (40% at the end of fermentation), but from an applied and enological point of view it is still desirable to improve this trait. In order to enhance malic acid consumption, cells were transformed with genetic constructs containing both Kluyveromyves lactis dicarboxylate permease KlJEN2 and the MAE2 malic enzyme from Schizosaccharomyces pombe under constitutive expression. Data will be presented showing how the physiology of malic acid utilization is associated with the distinct yeast genetic backgrounds.